2007
DOI: 10.1097/01.mcd.0000228418.74413.52
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic overlap in Melnick–Needles, serpentine fibula–polycystic kidney and Hajdu–Cheney syndromes: a clinical and molecular study in three patients

Abstract: Several disorders characterized primarily by anomalies of the skeleton have recently been shown to be caused by mutations in the X-linked gene, FLNA. One of these conditions, the Melnick-Needles syndrome exhibits a phenotype that shares overlap with that of serpentine fibula-polycystic kidney syndrome and the autosomal dominant condition, Hajdu-Cheney syndrome. Here, we describe three individuals with these diagnoses. The individual with serpentine fibula-polycystic kidney syndrome, the fifth case reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Most likely HCS is caused by a gene defect. FLNA, FLNB, and FLNC genes, encoding filamin A, B, and C, respectively, were excluded earlier as causative genes in a single HCS patient [Albano et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Most likely HCS is caused by a gene defect. FLNA, FLNB, and FLNC genes, encoding filamin A, B, and C, respectively, were excluded earlier as causative genes in a single HCS patient [Albano et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…12 Ramos et al 11 compared the phenotype of SFPKS with HCS and concluded that ascertainment bias had led to the delineation of SFPKS as a distinct condition. Two additional cases of SFPKS were subsequently reported in female patients 7,13 and both authors concluded that HCS and SFPKS are likely to be allelic. Both individuals described here are heterozygous for truncating mutations in exon 34 of NOTCH2, similar to those identified in individuals with HCS.…”
Section: Discussionmentioning
confidence: 99%
“…Case one 5 was originally reported as an example of familial SFPKS, but her phenotype has evolved into a more typical HCS presentation complete with acrosteolysis. Case two 7 presented with marked serpentine fibulae and lacks acro-osteolysis, but many of her other phenotypic features were typical of the HCS phenotype. The phenotypic overlap between HCS and SFPKS was first noted in a description of a cohort of individuals with HCS and polycystic kidney syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations